Antimicrobial Activity of Chlorhexidine, Peracetic acid/ Peroxide hydrogen and Alcohol based compound on Isolated Bacteria in Madani Heart Hospital, Tabriz, Azerbaijan, Iran - Reza Ghotaslou; Nashmil Bahrami (Tabriz University of Medical Sciences, 2012)
Purpose: The aim of present study was to investigate the effect of chemical agents on the clinical isolates in Madani Heart Hospital, Tabriz, Iran. Methods: The minimum bactericide concentration (MBC) of disinfectants including chlorhexidine (Fort), peracetic acid (Micro) and an alcohol based compound (Deconex) on selected bacteria at various dilutions were determined by the standard suspension technique. Results: MBC of Micro, Fort and Deconex were 2-128 mg/L, 2-64 mg/L and 4 - 32 mg/L, respectively. The Gram negative bacteria were more resistance to disinfectant relation to Gram positive bacteria. Conclusion: The results showed that these agents are able to eradicate the bacteria and they can be used lonely.